2016
DOI: 10.1002/2015ja022013
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of forbidden oxygen lines in the inner coma of 67P/Churyumov‐Gerasimenko

Abstract: Observations of the green and red‐doublet emission lines have previously been realized for several comets. We present here a chemistry‐emission coupled model to study the production and loss mechanisms of the O(1S) and O(1D) states, which are responsible for the emission lines of interest for comet 67P/Churyumov‐Gerasimenko. The recent discovery of O2 in significant abundance relative to water 3.80 ± 0.85% within the coma of 67P has been taken into consideration for the first time in such models. We evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…The modelling work of Cessateur et al (2016a) has suggested that O 2 can play a significant role in determining the [OI] G/R ratio. By incorporating a small O 2 abundance, of 1% of the CO production rate, we find that the contribution of O 2 dissociative excitation is very small (more than two orders of magnitude to the total) in producing O( 1 S) whereas it is the third most important source of O( 1 D) for radial distances above 30 km (see Fig 4).…”
Section: Effect Of the Neutral Species Abundancesmentioning
confidence: 99%
See 1 more Smart Citation
“…The modelling work of Cessateur et al (2016a) has suggested that O 2 can play a significant role in determining the [OI] G/R ratio. By incorporating a small O 2 abundance, of 1% of the CO production rate, we find that the contribution of O 2 dissociative excitation is very small (more than two orders of magnitude to the total) in producing O( 1 S) whereas it is the third most important source of O( 1 D) for radial distances above 30 km (see Fig 4).…”
Section: Effect Of the Neutral Species Abundancesmentioning
confidence: 99%
“…These studies also constrained the photodissociation yield of water producing O( 1 S) at Lyman-α wavelength as about 1% of the total absorption cross section. After detection of molecular oxygen in comets 67P-Churyumov-Gerasimenko (Bieler et al 2015;Altwegg et al 2019) and 1P/Halley (Rubin et al 2015), the photochemical model developed by Cessateur et al (2016a) has shown that not considering the role of O 2 in the photochemistry of [OI] emissions leads to an underestimation of the CO 2 abundance in comets.…”
Section: Introductionmentioning
confidence: 99%
“…Those lines are produced by prompt emission following the photodissociation of various parent molecules (H 2 O, CO 2 , CO, but also O 2 ) into a shortlived excited oxygen atoms (Festou and Feldman 1981;Cessateur et al 2016). The combination of measurements of two forbidden lines O 1 D and O 1 S shows that is possible to even estimate the CO 2 /H 2 O ratio (McKay et al 2012;Decock et al 2013;Cessateur et al 2016). The 6300.304 Å line, which is the brightest of the three forbidden oxygen lines has been successfully used to derive water production rates (e.g., Spinrad 1982;McKay et al 2012).…”
Section: Uv/visible Emission Featuresmentioning
confidence: 99%
“…The photoionization of these neutrals by the solar extreme ultraviolet radiation (EUV) has been assumed to be the main source of ionization near comets (Mendis et al 1985), although both charge exchange with the solar wind protons and electron impact ionization have also been suggested (Wallis 1973;Kim & Huntress 1975;Kimura et al 2000;Tinck & Bogaerts 2016;López-Patiño et al 2017). The charge exchange between CO and H 2 O + at small distances and the reaction between CO and H 2 CO + at large distance from the cometary nucleus can contribute to CO + production (Haider & Bhardwaj 2005;Cessateur et al 2016). The high density of electrons and molecular ions in the cometary coma facilitates the reactive processes among them, such as the dissociative recombination (DR).…”
Section: Introductionmentioning
confidence: 99%